2009
DOI: 10.1002/cmdc.200800427
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Based Optimization of Benzoic Acids as Inhibitors of Protein Tyrosine Phosphatase 1B and Low Molecular Weight Protein Tyrosine Phosphatase

Abstract: We have optimized previously discovered benzoic acids 1, which are active as inhibitors of PTP1B and LMW-PTP, two protein tyrosine phosphatases that have emerged as attractive targets for the development of novel therapeutic agents for the treatment of diabetes, obesity, and cancer. Our efforts led to the identification of new and more potent analogues with appreciable selectivity toward human PTP1B and the IF1 isoform of human LMW-PTP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 42 publications
1
31
0
1
Order By: Relevance
“…Molecular docking studies also indicated that these compounds interact with amino acid residues involved in the affinity and selectivity of inhibitors toward this enzyme. 104 Bhattarai et al identified TZD scaffolds as PTP 1B inhibitors by means of a computeraided drug design protocol involving virtual screening. A series of benzylidene-2, 4-thiazolidinedione derivatives with substitutions on the phenyl ring at the ortho or para positions of the thiazolidinedione (TZD) group were reported with IC 50 values in a low micromolar range.…”
Section: A Thiazolidinedionesmentioning
confidence: 99%
“…Molecular docking studies also indicated that these compounds interact with amino acid residues involved in the affinity and selectivity of inhibitors toward this enzyme. 104 Bhattarai et al identified TZD scaffolds as PTP 1B inhibitors by means of a computeraided drug design protocol involving virtual screening. A series of benzylidene-2, 4-thiazolidinedione derivatives with substitutions on the phenyl ring at the ortho or para positions of the thiazolidinedione (TZD) group were reported with IC 50 values in a low micromolar range.…”
Section: A Thiazolidinedionesmentioning
confidence: 99%
“…The synthesis of inhibitors 7aee and 8aee was carried out according to a previously reported procedure which is depicted in Scheme 1 [54,55].…”
Section: Chemistrymentioning
confidence: 99%
“…Interesting results have been achieved obtaining potent PTP inhibitors endowed with IC 50 values at submicromolar levels. They have been shown to act as competitive and reversible PTP inhibitors with significant selectivity for PTP1B and the IF1 isoform of LMW-PTP [53,54].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the identified competitive inhibitor 2 was active towards all tested PTPs, and similar 2,4-thiazolidinones have been recently described as PTP inhibitors. [21] According to our results, compound 2 is an unselective and competitive PTP inhibitor-K I values have been determined for the four PTPs (Scheme 1). Moreover, the nonselectivity of 2 is in agreement with the high homology of the active sites of PTPs.…”
Section: Resultsmentioning
confidence: 99%